2019
DOI: 10.7124/feeo.v24.1078
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the «mass of seeds from a plant» sign in the soybeans hybrids of the different groups of ripeness

Abstract: Aim. The purpose of the research is to determine the manifestation of the feature “seed weight from a plant” (the, parental forms) and hybrids, to establish the level of variability behind the soybean varieties in the F2–F5 hybrid combinations, to determine the effectiveness of selections for productivity in terms of the “seed weight from a plant” indicator from the hybrid populations of the F2–F5. Methods. The field, selection and genetic, calculation and comparative methods of the research were used. The var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Scientists have found that upon working to increase the adaptive potential of soybean varieties, it is possible to increase the annual collections of vegetable protein and oil by 10-15% or more (Vozhegova et al, 2019).…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…Scientists have found that upon working to increase the adaptive potential of soybean varieties, it is possible to increase the annual collections of vegetable protein and oil by 10-15% or more (Vozhegova et al, 2019).…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…У технологіях вирощування сільськогосподарських культур застосування під час вегетації комплексних мікродобрив на хелатній основі для позакореневого підживлення є важливим елементом підвищення урожайності [2,10]. Встановлено, що для росту та розвитку і ефективних продукційних процесів у рослинному організмі недостатньо застосовувати тільки органічні та мінеральні добрива без збалансованого надходження мікроелементів живлення [8,19]. Галузеві підприємства хімічної промисловості України тривалий час зовсім не виробляли комплексні мікродобрива, однак ринок агрохімікатів мав пропозицію численних закордонних виробників [12,18].…”
Section: вступunclassified